STUDI KASUS SISWA YANG MEMILIKI PRESTASI BELAJAR RENDAH KELAS VIIC SMP NEGERI 4 SUNGAI RAYA - Amalia, Yanti; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to find out and solve the problem of students who have low learning achievement at SMP Negeri 4 Sungai Raya. The case subjects in this research were 2 class VII C students who had low learning achievement. This research uses a qualitative research approach with descriptive methods in the form of case study research. This research uses data collection tools such as interviews, observation, documentation and home visits. From the results of this research, it can be concluded that the internal factors that cause students to have low learning achievement are a lack of motivation and interest in learning and the external factors are a lack of attention from both parents, a lack of communication between parents and children, and the condition of a broken home. The results after providing assistance to case subjects I and II were that the case subjects had shown good changes, the most important thing was that their learning scores in mathematics had received higher marks than before and the case subjects seemed more enthusiastic and focused on following class lessons, and submitted assignments well